Ultraviolet-induced free radical reactions in ENR50/alkyd blend leading to significant increase in cross-linking - Yoke, K.K.; Desmond, T.C.A.; Seng, N.G. (SAGE Publications, 2014)
In this work, the potential of palm stearin alkyd as a cross-linking agent for rubber compounding was investigated. Alkyd carrying pendent –COOH groups was blended with epoxidised natural rubber (ENR50) via solvent casting technique at ambient temperature. Spectroscopic characterisations show that ENR50 and alkyd have interacted with each other via chemical reaction involving the epoxide of the rubber and –COOH of alkyd. Consequently, notable increase in the glass transition temperature (Tg) and gel content of the blend was observed. In addition to the epoxide ring-opening reaction, the extent of cross-linking in the blend was further increased by means of ultraviolet (UV) curing. As a result, the UV-cured blends experienced lower percentage of swelling, produced higher percentage of gel, have higher cross-link density and higher Tg. The cross-link density in the rubber/alkyd blend has increased from 3.0 106 mol cm3 to 2.0 104 mol cm3 after UV curing. This is clearly evidenced from the swelling test results, where ENR and alkyd are completely soluble in the solvent, but upon blending and subsequent UV irradiation,the blend produced >90% of gel and swelled by 318%. Findings from this work show that sustainable material such as vegetable oil could be utilised in development of cross-linking agent for rubber. Significant increase in the cross-link density of the UVcured blend suggests that environment friendly compound such as alkyd has great potential to serve as an alternative to conventional compounds in rubber vulcanisation.